Response surface methodology integrated modeling of glass fiber reinforced polymer delamination in high speed drilling - Keong, Woo Tze (Asian Research Publishing Network, 2016)
Extensive research efforts has been made in the conventional drilling of glass fiber reinforced polymer, where most researches focused in the studies of drilling parameters and thrust force relationship to delamination and tool wear. The effect of drilling generated heat was suggested frequently in these studies, but not many in-depth researches was done in this area. In this paper, an experiment was performed to study the effects of thrust force and drilling generated temperature generated from drilling parameters on delamination factor. A response surface method (RSM) integrated model consist of two phases was developed. The first phase of RSM modelling explained the relationship of drilling parameters with thrust force and drilling generated heat as mediator. The relationship between the mediator and the delamination factor were developed in the second phase of RSM modeling. The final RSM integrated models were validated and it resulted in a low percentage error delamination factor estimation equation from drilling parameters, while understanding and controlling the thrust force and drilling generated temperature.